Pharmacoeconomic evaluation of artesunate-amodiaquine and artesunate- mefloquine artemisinin-based combination therapies. - G.K.A, Adepoju (Indian Journal of Pharmacy Practice)
These two artemisinin-combination therapies (ACTs) have been found to be rarely prescribed due to various reasons relating to both clinical and marketing promotional considerations. This study aims at uniting these factors by evaluating the pharmacoeconomic considerations on the choice of these two drugs. Published data on efficacy/ effectiveness trials were reviewed from where the data for this study were extracted. A pharmacoeconomic analysis was carried out using the various tools of pharmacoeconomics. It was found out that clinically derivable utilities and health outcomes (Side-effects and, probably, convenience of dosage regimen) did not favour the frequent choice of these drugs. Side effects and, probably, convenience of dosage regimen mainly affected the choice of these drugs.Clinical cure should not be the only health outcome to be guided in therapy. Other unfavourable health outcomes should be considered also. Disability/Distress to the patients should be considered also. However, Artesunate-Amodiaquine (AAQ) has a superior pharmacoeconomic advantage over Artesunate-Mefloquine (AM) in terms of cost and cost utility. Artesunate-Mefloquine (AM) has a higher cost-benefit than AAQ but this is rarely used in health considerations. Side effects of these drugs limit their choice as antimalarials. in effective in treating uncomplicated Plasmodium falciparum malaria
Keywords: Pharmacoeconomics; health outcomes; disability/distress scale; recrudescence; health utility